Investigating the Impact of Service Quality on Customer Satisfaction and Subsequent Customer Loyalty in Bank Jago - Siregar, Rachael Gracella Veronita; Kusumawati, Nurrani (Journal Integration of Management Studies, 2023)
In an increasingly competitive banking industry, it is important for banks to understand consumer satisfaction and build consumer loyalty in order to maintain market share and achieve sustainable growth. This research focuses on Bank Jago users, with the aim of analyzing the relationship between service quality, consumer satisfaction, and consumer loyalty in that context. This study uses a quantitative approach with purposive sampling method to collect and analyze data from 318 respondents who are Bank Jago users in the Bandung and Jabodetabek areas who have experience using Bank Jago services for at least 1 year. The data collection method was conducted through a questionnaire-based survey that was disseminated to a sample of bank users. The collected data were then analyzed using descriptive statistics and PLS-SEM to test the relationship between the observed variables. The results of the analysis show that service quality, especially in the indicators of Efficiency, Responsiveness, Site Organization, and User Friendliness provided by Bank Jago has a positive effect on customer satisfaction. The higher the quality of services provided by the bank, the higher the level of satisfaction felt by users. In addition, this study also revealed that consumer satisfaction has a positive influence on consumer loyalty in Bank Jago users. In other words, the more satisfied users are with the banking services provided by Bank Jago, the more likely they are to remain loyal as Bank Jago users in the future. This research makes an important contribution to Bank Jago in understanding the factors that affect the satisfaction and loyalty of their users. The findings of this research can be the basis for Bank Jago to improve the quality of their services, optimize user experience, and maintain consumer loyalty amid intense banking industry competition. In addition, this research also contributes to a broader understanding of the importance of service quality in creating consumer satisfaction and building consumer loyalty in the context of the banking industry.